2016
DOI: 10.5755/j01.ee.27.1.13198
|View full text |Cite
|
Sign up to set email alerts
|

Gamification as a Mean of Driving Online Consumer Behaviour: SOR Model Perspective

Abstract: Gamification recently attracted attention from practitioners and researchers aiming to gain understanding about gamification applicability. According to forecasts of various market research agencies, application of gamification in activities of companies increases and gamification market growth will continue in the future. As gamification is usually focused on customers, it is naturally related to consumer behaviour. However, there is a lack of studies approaching gamification from consumer behaviour perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 24 publications
1
66
0
Order By: Relevance
“…Game components are specific applications that can be seen and used in the game interface ( Hunter and Werbach, 2012 ) and can be considered particular instances of mechanics and dynamics ( Kuutti, 2013 ). Components act as stimulants and are often perceived directly from the consumer's perspective ( Gatautis et al., 2016 ).…”
Section: Theoretical Background On E-commerce and Gamificationmentioning
confidence: 99%
“…Game components are specific applications that can be seen and used in the game interface ( Hunter and Werbach, 2012 ) and can be considered particular instances of mechanics and dynamics ( Kuutti, 2013 ). Components act as stimulants and are often perceived directly from the consumer's perspective ( Gatautis et al., 2016 ).…”
Section: Theoretical Background On E-commerce and Gamificationmentioning
confidence: 99%
“…The benefits of implementing a comprehensive gamification framework encompass important hedonic outcomes, such as engagement, enjoyment and playfulness, fun and learning experiences (Cardador, Northcraft, & Whicker, 2017;Gatautis, Vitkauskaite, Gadeikiene, & Piligrimiene, 2016;Hamari & Koivisto, 2015;Harwood & Garry, 2015;Holbrook et al, 1984). Regardless of the value of engagement and motivation, gamification is much more than just a set of entertaining exercises and teamwork activities with no targets and organized outputs (Agogué et al, 2015;Dale, 2014;Kalinauskas, 2014).…”
Section: Gamification Elements and Outcomesmentioning
confidence: 99%
“…In fact, the benefits of gamification go beyond the hedonic elements as they also include utilitarian and social benefits. The utilitarian benefits encompass increased productivity among employees (Hamari & Koivisto, 2015), cognitive, functional, creative problem-solving, time to action, usefulness and ease of use (Gatautis et al, 2016;Hamari & Koivisto, 2015;Harwood & Garry, 2015;Stock, Oliveira, & Von Hippel, 2015), improved customer loyalty (Lucassen & Jansen, 2014), and accelerated product development processes (Agogué et al, 2015). The social benefits encompass people's reactions during interactive situations, recognition, social influence, and self-esteem (Hamari & Koivisto, 2015;Harwood & Garry, 2015).…”
Section: Gamification Elements and Outcomesmentioning
confidence: 99%
“…This model was initially developed in context of retail industry through which it was suggested that servicescape serves as a stimulus to shape and influence inner states of consumers and deriving certain kinds of consumer behavior. The SOR model (stimulus‐organism‐response) suggests that different environmental factors serve as stimulus (S) to influence the internal state of individual (O), which ultimately shapes the response/behavior of the individual (R) (Gatautis et al, 2016; Wang et al, 2019). This study attempts to examine the phenomenon through which the external stimuli leads towards a certain inner state of consumer such as brand love, BEQ, and EBE.…”
Section: Literature Reviewmentioning
confidence: 99%